Development and Effectiveness of Arabic Morphology Drill Book Based on Bloom's Taxonomy to Improve Students' Learning Outcomes.: راسة تدريبات الصرف على أساس تصنيف بلوم لترقية نتائج تعلم الصرف للفصل - Septian Kashogi; Hafidah; Siti Desi Hidayati (Ukazh : Journal of Arabic Studies, 2026)
In light of the continuous efforts to develop Arabic language teaching strategies and overcome the obstacles of morphological rules (Sarf), this research offers an innovative, practical pathway for designing instructional materials. The objectives of this research are to: (1) describe the procedures for developing a Sarf workbook based on Bloom’s Cognitive Taxonomy for seventh-grade students at the Muhammadiyah Islamic Boarding School Prambanan Yogyakarta, (2) describe the validity of the developed Sarf workbook, and (3) describe the effectiveness of this instructional tool. Research Methodology: The researcher employed an experimental field study utilizing the Research and Development (R&D) method based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection instruments used in this study were interviews, questionnaires, and tests. Research Results: The findings of the research align directly with its objectives and indicate the following: First (Procedures): The morphology (sharaf) workbook was developed in accordance with the ADDIE model across five sequential phases, beginning with the analysis of needs and problems, followed by the design and development of learning activities based on the cognitive levels of Bloom's Taxonomy (remembering, understanding, and applying). Second (Validity): The developed Sarf workbook was proven highly valid and suitable for instructional use in the educational process, based on the evaluation and validation results from expert judges. Third (Effectiveness): The workbook demonstrated significant effectiveness in improving the academic achievement of seventh-grade students. Based on the t-test statistical analysis, the researcher found that the significance value (Sig) was 0.00 (less than 0.05), indicating that the hypothesis is accepted; thus, there is a substantial positive impact and high effectiveness in using this workbook.